Research Paradigms for Accounting: A Review - Ismail, Kamisah; Zainuddin, Suria (Asian Journal of Accounting Perspectives, 2013)
This paper reviews research paradigms that have existed since the 1970s. Specifically, it reviews two frameworks by Burrell and Morgan (1979) and Chua (1986) that have become prominent as a basis for methodological stance in accounting and management research. These research paradigms or perspectives determine the research methodology applied in this study. Different schools of thought have their own views and arguments. Thus, there is no one best research method to use because every method has its own strengths and weaknesses.